Analysis current ratio return on asset and debt to equity ratio on dividend payout ratio - Metyria Imelda Hutabarat; Harlen Silalahi; Hendrik Elisa Sutejo Samosir; Muhammad Raja Siregar; Hanna Meilani Damanik (Enrichment : Journal of Management, 2023)
The distribution of dividend payments showed the state of the company's performance. The research aimed to found out the results of financial ratios to the Dividend Payout Ratio for food and beverage companies on the Indonesia Stock Exchange. The research period was taken from 2016 to 2021. Data collection in this research used secondary data in the form of data collection from the company's annual financial reports published on the Indonesia Stock Exchange. The analytical method uses multiple linear regression. The results of the research showed that the Current Ratio had positive but not significant effect on the Dividend Payout Ratio. Return on Assets partial results had positive and significant effect on the Dividend Payout Ratio. Debt to Equity Ratio was partially proven to had no significant negative effect on the Dividend Payout Ratio. Simultaneous test showed that the Current Ratio, Return on Assets and Debt to Equity Ratio had positive and significant effect on the Dividend Payout Ratio. The urgency of research in knowing the results of financial ratios on the Dividend Payout Ratio in order to attract the attention of investors to invest more so that the issuer's capital will also increase which makes the company grow. The research contribution will give a signal to the public and those who wish to know the Dividend Payout Ratio of food and beverage companies.